Active blended learning management in music subject based on the hybrid learning framework for primary 4 students at Ban Nong Du School, Thawat Buri District, Roi Et Province - Kaewsrisai, Kamonchanok (Linguistics and Culture Review, 2022)
The objectives of this research were 1) to develop an active blended learning management plan in Music subject based on the hybrid learning framework to be effective according to 80/80 criteria, 2) to compare the students' academic achievement between pretest and posttest periods, and 3) to study the satisfaction of students towards the active blended learning management in music subject based on the hybrid learning framework. The target group of this research was the 14 primary 4 students of Ban Nong Du School. Thawat Buri District, Roi Et Province in semester 1, academic year 2021, which was selected from purposive sampling. The research instruments were: 1) the index of conformity (IOC) of the music learning management plan according to the hybrid learning framework was 0.87. This showed that experts are of the opinion that an effective learning management plan can be implemented. 2) The achievement test was a 30-item, four-choice test. The test had a difficulty and power value classified between 0.41-0.60, which was appropriate and could be tested. 3) A questionnaire on the satisfaction of students towards active blended learning management in music subject based on the hybrid learning framework consisted of 15 items.